Unleashing Ferroptosis in Human Cancers: Targeting Ferroptosis Suppressor Protein 1 for Overcoming Therapy Resistance - Jaewang Lee; Jong-Lyel Roh (MDPI AG, 2023)
Ferroptosis, a recently identified form of regulated cell death characterized by the iron-dependent accumulation of lethal lipid peroxidation, has gained increasing attention in cancer therapy. Ferroptosis suppressor protein 1 (FSP1), an NAD(P)H-ubiquinone oxidoreductase that reduces ubiquinone to ubiquinol, has emerged as a critical player in the regulation of ferroptosis. FSP1 operates independently of the canonical system xc-/glutathione peroxidase 4 pathway, making it a promising target for inducing ferroptosis in cancer cells and overcoming ferroptosis resistance. This review provides a comprehensive overview of FSP1 and ferroptosis, emphasizing the importance of FSP1 modulation and its potential as a therapeutic target in cancer treatment. We also discuss recent progress in developing FSP1 inhibitors and their implications for cancer therapy. Despite the challenges associated with targeting FSP1, advances in this field may provide a strong foundation for developing innovative and effective treatments for cancer and other diseases.